2016
DOI: 10.3389/fevo.2016.00047
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Lipocalins (MUP, OBP, LCN) Are Co-expressed in Tissues Involved in Chemical Communication

Abstract: Chemical communication is mediated by signal production and signal perception and in house mice (Mus musculus), both processes involve lipocalin proteins (OBP, MUP, LCN) that transport volatiles and protect them in tissues where they are produced. However, potential roles of lacrimal, nasal, and salivary lipocalins are still not well known. We aimed to determine the expression of the recently described family of odorant binding proteins (Obp), along with major urinary proteins (Mup) across different tissues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 69 publications
5
52
4
Order By: Relevance
“…3D, 3E) are in agreement with our proteomic analysis in this study and with our previously published study using qPCR (Stopkova et al, 2016). Our simple RNAseq analysis revealed the expression of Obp8 which was previously detected only with bioinformatics tools (Stopková et al, 2009; Stopkova et al, 2016), thus providing the first evidence for the expression of Obp8 transcript. Interestingly, OBP1 was one of the most abundant tear proteins in individuals of both sex.…”
Section: Resultssupporting
confidence: 92%
“…3D, 3E) are in agreement with our proteomic analysis in this study and with our previously published study using qPCR (Stopkova et al, 2016). Our simple RNAseq analysis revealed the expression of Obp8 which was previously detected only with bioinformatics tools (Stopková et al, 2009; Stopkova et al, 2016), thus providing the first evidence for the expression of Obp8 transcript. Interestingly, OBP1 was one of the most abundant tear proteins in individuals of both sex.…”
Section: Resultssupporting
confidence: 92%
“…We also show that many nasal and lacrimal proteins are abundant in the saliva proteome, presumably as a consequence of their final transport to the oral cavity from tissues where they are expressed and where they function as VOC transporters. These include a group of odorant binding proteins (OBP) that we previously identified as predicted transcripts in the mouse genome2733, detected their expression sites in various oro-facial tissues31, and finally detected them as proteins in the saliva proteome in this study. Because OBPs, MUPs and LCNs have similar tertiary structure (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…We have also provided evidence that Obp transcripts are co-expressed in combination with other lipocalin transcripts (e.g. nasal and lacrimal Obp5 and Obp7 with Mup4 and Lcn11 ), presumably to widen the spectrum of ligands that OBP, MUP, and LCN proteins may sequester and transport31. Thus, this study also aims to detect particular OBPs in the mouse saliva to test whether OBPs are involved in the transport of VOCs and various degradation products from the nasal and lacrimal tissues to the oral cavity where digestion starts.…”
mentioning
confidence: 75%
“…Only one marker located on the centromeric edge of the MUP cluster showed allelic diversity comparable to that of outside markers, though heterozygosity at this marker was very low. This marker does not reflect overall MUP diversity inside the cluster, and interestingly, it is located close to Mup4 , which is expressed in lacrimal glands and olfactory mucosa16, and may have different functions than urinary MUPs. The only other study utilizing microsatellite markers to infer MUP diversity to our knowledge suggested that MUPs are highly polymorphic and provide the genetic basis for kin recognition and inbreeding avoidance4.…”
Section: Discussionmentioning
confidence: 93%